Design space exploration and performance modelling of advanced turbofan and open-rotor engines - Giannakakis, Panagiotis (Cranfield University, 2013)
This work focuses on the current civil engine design practice of increasing overall pressure ratio, turbine entry temperature and bypass ratio, and on the technologies required in order to sustain it. In this context, this thesis contributes towards clarifying the following gray aspects of future civil engine development: the connection between an aircraft application, the engine thermodynamic cycle and the advanced technologies of variable area fan nozzle and fan drive gearbox. the connection between the engine thermodynamic cycle and the fuel consumption penalties of extracting bleed or power in order to satisfy the aircraft needs. the scaling of propeller maps in order to enable extensive open-rotor studies similar to the ones carried out for turbofan engines. The rst two objectives are tackled by implementing a preliminary design framework, which comprises models that calculate the engine uninstalled performance, dimensions, weight, drag and installed performance. The framework produces designs that are in good agreement with current and near future civil engines. The need for a variable area fan nozzle is related to the fan surge margin at take-o , while the transition to a geared architecture is identi ed by tracking the variation of the low pressure turbine number of stages. The results show that the above enabling technologies will be prioritised for long range engines, due to their higher overall pressure ratio, higher bypass ratio and lower speci c thrust. The analysis also shows that future lower speci c thrust engines will su er from higher secondary power extraction penalties. A propeller modelling and optimisation method is created in order to accomplish the open-rotor aspect of this work. The propeller model follows the lifting-line approach and is found to perform well against experimental data available for the SR3 prop-fan. The model is used in order to predict the performance of propellers with the same distribution of airfoils and sweep, but with di erent design point power coe cient and advance ratio. The results demonstrate that all the investigated propellers can be modelled by a common map, which separately determines the ideal and viscous losses.